Respuesta :

Answer:

Step-by-step explanation:

4). m(arc GJ) = 90°

5). m(arc HI) = m(arc JH) - m(arc JI)

                    = 180° - 151°

                    = 29°

6). m(arc HIJ) = 180°

7). m(arc GJI) = m(arc GJ) + m(arc JI)

                      = 90° + 151°

                      = 241°

8). m(arc GHJ) = m(arc GH) + m(arc HI) + m(arc IJ)

                        = 90° + 29° + 151°

                        = 170°

9). m(arc GJH) = 360° - m(arc GH)

                        = 360° - 90°

                        = 270°

10). m(arc HGJ) = 180°

11). m(arc GH) = 90°

12). m(arc GHI) = m(arc GH) + m(arc HI)

                        = 90° + 29°

                        = 119°

13). m(arc HJI) = 360° - m(arc HI)  

                       = 360° - 29°

                       = 331°

14). m(arc JHI) = m(arc JH) + m(arc HI)

                       = 180° + 29°

                       = 209°

15). m(arc JIG) = 360° - m(arc JG)

                       = 360° - 90°

                       = 270°

The measures of each arc in the circle shown in the diagram are:

4. [tex]\mathbf{\widehat{GJ} = 90^{\circ}}[/tex] (right angle)

5. [tex]\mathbf{\widehat{HI} = 29^{\circ}}[/tex]

6. [tex]\mathbf{\widehat{HIJ} = 180^{\circ}}[/tex] (semicircle = 180°)

7. [tex]\mathbf{\widehat{GJI} = 241^{\circ}}[/tex]

8. [tex]\mathbf{\widehat{GHJ} = 270^{\circ}}[/tex]

9. [tex]\mathbf{\widehat{GJH} = 270^{\circ}}[/tex]

10. [tex]\mathbf{\widehat{HGJ} = 180^{\circ}}[/tex] (semicircle = 180°)

11.  [tex]\mathbf{\widehat{GH} = 90^{\circ}}[/tex] (right angle)

12. [tex]\mathbf{\widehat{GHI} = 119^{\circ}}[/tex]

13. [tex]\mathbf{\widehat{HJI} = 331^{\circ}}[/tex]

14. [tex]\mathbf{\widehat{JHI} = 209^{\circ}}[/tex]

15. [tex]\mathbf{\widehat{JIG} = 270^{\circ}}[/tex]

Recall:

  • Measure of a full circle = 360°

Given circle with center B, thus:

4. [tex]\mathbf{\widehat{GJ} = 90^{\circ}}[/tex] (right angle)

5. [tex]\widehat{JI} = 151^{\circ}[/tex] (given)

[tex]\widehat{JI} + \widehat{HI} = 180^{\circ}[/tex] (semicircle = 180°)

  • Substitute

[tex]151 + \widehat{HI} = 180^{\circ}\\\\\widehat{HI} = 180 - 151\\\\\mathbf{\widehat{HI} = 29^{\circ}}[/tex]

6. [tex]\mathbf{\widehat{HIJ} = 180^{\circ}}[/tex] (semicircle = 180°)

7. [tex]\widehat{GJI} = \widehat{GJ} + \widehat{JI}[/tex]

  • Substitute

[tex]\widehat{GJI} =90 + 151\\\\\mathbf{\widehat{GJI} = 241^{\circ}}[/tex]

8. [tex]\widehat{GHJ} = \widehat{GH} + \widehat{HIJ}[/tex]

  • Substitute

[tex]\widehat{GHJ} =90 + 180\\\\\mathbf{\widehat{GHJ} = 270^{\circ}}[/tex]

9. [tex]\widehat{GJH} = \widehat{GJ} + \widehat{HIJ}[/tex]

  • Substitute

[tex]\widehat{GJH} =90 + 180\\\\\mathbf{\widehat{GJH} = 270^{\circ}}[/tex]

10. [tex]\mathbf{\widehat{HGJ} = 180^{\circ}}[/tex] (semicircle = 180°)

11.  [tex]\mathbf{\widehat{GH} = 90^{\circ}}[/tex] (right angle)

12.  [tex]\widehat{GHI} = \widehat{GH} + \widehat{HI}[/tex]

  • Substitute

[tex]\widehat{GHI} =90 + 29\\\\\mathbf{\widehat{GHI} = 119^{\circ}}[/tex]

13.  [tex]\widehat{HJI} = 360 - \widehat{HI}[/tex]

  • Substitute

[tex]\widehat{HJI} =360 - 29\\\\\mathbf{\widehat{HJI} = 331^{\circ}}[/tex]

14. [tex]\widehat{JHI} = 360 - \widehat{JI}[/tex]

  • Substitute

[tex]\widehat{JHI} =360 - 151\\\\\mathbf{\widehat{JHI} = 209^{\circ}}[/tex]

15. [tex]\widehat{JIG} = 360 - \widehat{GJ}[/tex]

  • Substitute

[tex]\widehat{JIG} =360 - 90\\\\\mathbf{\widehat{JIG} = 270^{\circ}}[/tex]

Learn more here:

https://brainly.com/question/23535384